Digitalised higher education: key developments, questions, and concerns - Komljenovic, Janja; Birch, Kean; Sellar, Sam; Bergviken Rensfeldt, Annika; Deville, Joe; Eaton, Charlie; Gourlay, Lesley; Hansen, Morten; Kerssens, Niels; Kovalainen, Anne; Nappert, Pier-Luc; Noteboom, Joe; et al. (Taylor & Francis, 2025)
Higher education is already profoundly digitalised. Students, academics, and university administrators routinely use digital technologies, many of which rely on data, including artificial intelligence. Universities aim to operate as data-powered organisations to support institutional efficiency and the personalisation of learning and student experience. These developments are occurring against the backdrop of university digital infrastructure moving to the cloud and the increasing role of ‘Big Tech’ in the sector. However, there are many unknowns about the aggregate impact of digitalisation on the sector, and hence, questions about potential risks and harms remain unanswered. Our approach in this collective piece is to reflect on particularly relevant and impactful dynamics of higher education digitalisation. We first identify assetisation as an emergent mode of governance linked to the digitalisation of HE, which brings new temporal, relational, and lock-in challenges for universities and their constituents. Second, we examine the macro-level structural transformation of higher education with the increasing role of Big Tech and Big EdTech. We conclude by discussing the consequences of the identified macro power dynamics.